Low Temperature magnetic properties of GdCoIn5 - Betancourth, D.; Facio, J.I.; Pedrazzini, P.; Jesus, C.B.R.; Pagliuso, P.G.; Vildosola, V.; Cornaglia, P.S.; García, D. J.; Correa, V. F.; Correa, Víctor Félix; Pedrazzini, Pablo (Elsevier, 2015)
Fil: Betancourth, D. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina